2020
DOI: 10.1039/d0cc05478j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically tuning transient silicone polymer networks with hydrogen bonding

Abstract: Hydrogen bonds on a silicone polymer permit supramolecular silicones to form transient polymer networks with energy absorbing properties that depend on the number of available OH groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Rheological measurements showed that, with increasing angular frequency, the viscosity of T-Vi79-SG builds until there is a crossover of G ′/ G ′′ that indicates, above these frequencies, the material is behaving as an elastomer (Figure B). This behavior is analogous fashion to other sugar silicones. , That is, the presence of the SCH 2 CH 2 in the amine sulfide polymers is, at most, a minor player in affecting the physical properties of the polymer.…”
Section: Results and Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Rheological measurements showed that, with increasing angular frequency, the viscosity of T-Vi79-SG builds until there is a crossover of G ′/ G ′′ that indicates, above these frequencies, the material is behaving as an elastomer (Figure B). This behavior is analogous fashion to other sugar silicones. , That is, the presence of the SCH 2 CH 2 in the amine sulfide polymers is, at most, a minor player in affecting the physical properties of the polymer.…”
Section: Results and Discussionsupporting
confidence: 52%
“…This behavior is analogous fashion to other sugar silicones. 28,41 That is, the presence of the SCH 2 CH 2 in the amine sulfide polymers is, at most, a minor player in affecting the physical properties of the polymer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unprecedented properties are attributed to the dynamic nature of supramolecular bonds, whose energies are low enough to allow bond exchanging under mild conditions. Various types of noncovalent interactions, such as hydrogen bonding, [11,12] ionic bonding, [13][14][15][16][17] and metal-ligand coordination, [18][19][20][21][22] have been exploited to build supramolecular silicone materials. Typical examples are thermoplastic elastomers of poly(siloxane-urethane) [23,24] and poly(siloxane-urea), [25,26] where the hydrogen bonding of urethane/urea units and the phase separation between soft polysiloxane segments and hard polyurethane/polyurea are responsible for their excellent mechanical properties and thermoplastic abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction is normally rather facile to practice and is primarily limited by issues of miscibility [ 20 , 21 ]. Sugar-silicone fluids can exhibit a variety of interesting properties, including the ability to effectively dissipate energy [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%